Purpose, Meaning and Alignment: Dual frameworks to scaffold understanding and design of assessment to enhance the student and teacher experience - Janssen, Amanda; Rowen, Roslyn (Journal of Academic Language and Learning, 2016)
Assessments are sometimes ambiguous and not always aligned to learning outcomes or rubrics, causing confusion between stakeholders. At Charles Darwin University (CDU) this problem is often first identified by students, where during one-on-one consultations with the Academic Language and Learning (ALL) team, they present with questions seeking clarification on the purpose and meaning of an assessment task. While these tasks would often benefit from re-wording, they cannot be altered in the current delivery of the course. To help address this problem, two inter-related frameworks have been developed: the Assessing Assessment (AA) framework 1 is used to diagnose where assessments are lacking in purpose, meaning and alignment; and the Challenge/Support (C/S) framework 2 uses the above diagnosis to plan for the necessary ALL support to ensure a challenging yet achievable task. This paper describes the frameworks and their development and discusses their application through a case study. The paper suggests that beyond the practicality of using the frameworks in a responsive way to provide ‘just-in-time’ curriculum-integrated student learning support, they also have the potential to be used in a proactive way to improve assessment design and plan for integrated ALL support where problems can be pre-empted. This transition from a temporary to a long-term application is discussed.